Evaluation of Immune Characteristics and Factors Associated with Immune Response following Hepatitis B Vaccination among Ghanaian Adolescents - Samuel Asamoah Sakyi; Joseph Badu Gyapong; Ebenezer Krampah Aidoo; Alfred Effah; Simon Koffie; Oscar Simon Olympio Mensah; Isaac Arddey; Godwin Boakye; Stephen Opoku; Benjamin Amoani; Robert Amadu Ngala (Advances in Virology)
Background. WHO recommends HBV-negative babies in high-prevalence (8%) countries receive anti-HBV vaccination. Ghana initiated mass immunization in 2002, but concerns remain about vaccine effectiveness and long-term protection. We evaluated immune characteristics and factors following hepatitis B vaccination among Ghanaian adolescents who received HBV vaccines. Methods. In this longitudinal cross-sectional study, 74 participants were enrolled from the Kumasi Metropolis, Ghana. Sociodemographic and lifestyle characteristics of participants were obtained using a questionnaire. Blood samples were obtained before and after booster administration for anti-HBsAg, IL-6, and IL-10 estimations using ELISA kit (Shanghai Chemical Ltd., China). Anti-HBsAg titers ≥10 mIU/ml were considered protective. Statistical analyses were done using SPSS version 26.0 and R programming language, p<0.05 was considered statistically significant. Results. We found 100% seroconversion rate, with 25.7% seroprotection rate (anti-HBsAg >10 mIU/ml). Gender (p=0.009), age (p=0.001), and exercising (p=0.044) were significantly associated with seroprotection. Following booster administration, 59.4% were hyporesponders (10 ≤ anti-HBsAg titre ≤99 mIU/ml) whilst 40.6% were good responders (anti-HBsAg titre ≥100 mIU/ml). Exercise (p=0.034) was significantly associated with immune response after booster administration. Moreover, we reported significant positive correlation between cytokines [IL-6 (r = 0.817, p<0.001) and IL-10 (r = 0.928, p<0.001)] and anti-HBsAg titre. Conclusion. Approximately two thirds of adolescents vaccinated at birth lack protective levels of antibodies against hepatitis B virus. Booster vaccines could aid in mounting protective levels of anti-HBsAg. Physical exercise was negatively associated with immune response to hepatitis B vaccinations.